Legitimizing illegitimacy revisiting illegitimacy in the Philippines and arguing for declassification of illegitimate children as a statutory class (Philippine Law Journal, 2014)
This paper, divided into three parts, expounds on the development of illegitimacy as a legal concept, in the process inviting a critical look: into the statutory classification vis-à-vis constitutional law precepts and modern developments in human rights and child rights law. Part I traces the historical development of illegitimacy in both civil and common law traditions, highlighting the moral underpinnings of the present socio-legal policies concerning illegitimate children. Part II focuses on the legal treatment of illegitimate children in the Philippines, noting that while there is an overall progress towards recognition of equality, illegitimate children remain disadvantaged in areas such as family law and succession. In Part III, the paper presents arguments for declassification, applying both "classic" and "new" equal protection treatments; the legal effects of recent treaty obligations of the Philippines; and the international trend towards amelioration of illegitimate children as a class. The paper concludes by reconciling the human rights precept of non-discrimination with the Constitutional mandate on protection of the family.